Prognostic Implications of Red Blood Cell Distribution Width to Albumin Ratio in Myelofibrosis: A 10-Year Multicenter and Retrospective Study - Zeng T; Zheng Z; Qian H; Liu L; Shi X; Shao Y; Huang Z; Li R; Wen B; Han Q; Feng Q; Tu L; et al. (Journal of Inflammation Research, 2025)
Tian Zeng,1,* Zhikang Zheng,1,2,* Honglan Qian,3,* Lirong Liu,4,* Xiaowei Shi,5,* Yanping Shao,6,* Zhaohao Huang,7 Rumeng Li,1 Bingbing Wen,1 Qingmei Han,1,8 Qiutian Feng,1,2 Lingrong Tu,1,2 Xiaojing Bao,1,2 Hongyan Tong,1 Jie Jin,1 Jian Huang1 1Department of Hematology, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Hematology, The Fourth Affiliated Hospital, Zhejiang University School of Medicine, Yiwu, Zhejiang, People’s Republic of China; 3Department of Hematology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 4Department of Hematology, The Affiliated Hangzhou First People’s Hospital, Westlake University School of Medicine, Hangzhou, Zhejiang, People’s Republic of China; 5Department of Hematology, The Affiliated People’s Hospital of Ningbo University, Ningbo, Zhejiang, People’s Republic of China; 6Department of Hematology, Taizhou Hospital of Zhejiang Province affiliated to Wenzhou Medical University, Taizhou, Zhejiang, People’s Republic of China; 7Department of Hematology, Xiangshan First People’s Hospital, Ningbo, Zhejiang, People’s Republic of China; 8Department of Pathology, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Huang, Department of Hematology, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310003, Zhejiang, People’s Republic of China, Email househuang@zju.edu.cn Hongyan Tong, Department of Hematology, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310003, Zhejiang, People’s Republic of China, Email tonghongyan@zju.edu.cnIntroduction: Myelofibrosis (MF) is a rare myeloproliferative neoplasm (MPN) characterized by significant mortality and limited predictive biomarkers. The red cell distribution width to albumin ratio (RAR), a novel biomarker indicative of inflammation, has emerged as a strong prognostic indicator in the general population but remains unexplored in MF.Methods: We retrospectively enrolled 504 consecutive MF patients from 7 hematological centers over a 10-year period. Multivariate Cox regressions were performed to assess the prognostic value of the RAR. Kaplan-Meier and restricted cubic splines (RCS) analyses were further performed to examine the associations between RAR and outcomes. Interaction and subgroup analyses were conducted to explore potential effect modifiers. We developed a predictive nomogram combining RAR and DIPSS-plus, with its incremental improvements assessed by discrimination and calibration metrics.Results: Patients who experienced leukemic transformation and death had significantly higher RAR levels. RAR remained an independent predictor of poor survival (adjusted HR: 1.58, 95% CI: 1.36– 1.85). RCS further suggested a positive non-linear association between RAR and overall survival. Adding RAR to DIPSS-plus score significantly improved prediction accuracy, as shown by an increased C-index from 0.709 to 0.762, a net reclassification improvement (31.1%, p = 0.004), and an integrated discrimination improvement (6.80%, p < 0.001). The refined model also demonstrated a significantly improved goodness of fit, as evidenced by a likelihood ratio test (p < 0.001) and reductions in AIC and BIC values.Conclusion: This large, multi-center cohort study is the first to reveal the prognostic significance of RAR in MF. The modified predictive nomogram combining DIPSS-plus score and RAR enhances prognostic discrimination and calibration, providing a simple yet cost-effective tool for refined risk stratification, especially in resource-limited settings.Keywords: myelofibrosis, inflammation, nutrition, prognosis, the red cell distribution width to albumin ratio